Pengembangan Sistem Penghantaran Obat Solid Self-Emulsifying Mikropartikel Gliklazid untuk Meningkatkan Disolusi - Suryani, Mega; Sutriyo, Sutriyo (UI Scholars Hub, 2011)
Gliclazide is a Hypoglycemicdrug, second-generation sulfonylurea used in the treatment of non insulin dependent diabetes mellitus. Gliclazide exhibit poor aqueous solubility, so that their low bioavailability. Objectivesthis study is to develop solid self-emulsifying (SE) microparticles of poorly soluble gliclazide to dissolution enchancement. These microparticles were prepared by spray drying method, using three surfactant (acripol, tween 80 and sodium lauryl sulphate) with various concentration. SE microparticles characterized in terms of morphology (SEM), particle size distribution (PSA), x-ray diffraction (XRD), thermal analysis (DSC), functional group analysis (FTIR), solubility test, and dissolution test. The all gliclazide SE microparticlesexhibited particle size smaller than pure gliclazide. The dissolution rate of gliclazide SE microparticles at one hour was increased about 2 to 3 times than gliclazide.